Turbulent flow and heat transfer behaviors in a circular tube fitted with multiple V–baffles - Chompookham, Teerapat; Promvonge, Pongjet; Skullong, Sompol; Siriwan, Narin; Bubphachot, Bopit; Wansasueb, Kittinan; Promthaisong, Pitak (My University, 2023)
This article presents turbulent flow patterns and thermal behaviors in a circular tube mounted with 30° multiple V–baffles. The influences of V–baffle numbers (N) of 2, 3 and 4 with pitch ratios (PR) of 1.0, 1.5 and 2.0 for Reynolds number (Re) between 3000 and 20,000 were investigated numerically at a fixed blockage ratio, BR = 0.05. These simulated results were proposed in four sections: numerical validations, flow and thermal characteristics and thermal performance. It was visible that the multiple V–baffles can help induce the impinging jet leading to disrupting the boundary layer, increasing the fluid mixing, and then enhancing the heat transfer above the plain tube alone. The rises of the number of V–baffles and the lower baffle pitch length led to raising the heat transfer and friction loss. The maximum thermal performance was obtained around 2.06 at N = 4, PR = 1.0 and lower Re.
Keywords: Circular tube; Heat transfer; Multiple V–baffle; Turbulent flow